The cultural politics of emotion - Laia Oliver-Frauca (Documents d'Anàlisi Geogràfica)
AHMED, Sara (2004) The cultural politics of emotion. Edinburgh: Edinburgh University Press, 224 p. ISBN 0-7486-1847-3